Comparing the Antiemetic Effects of Maropitant and Ondansetron in Cats with Acute Vomiting in Clinical Practice: Maropitant and ondansetron in acute vomiting - Karata Baykurt, T; Erdogan, H; Ural, K; Erdogan, S (Journal of the Hellenic Veterinary Medical Society, 2025)
The objective of this study is to compare the clinical efficacy of a single subcutaneous administration of maropitant and ondansetron in cats presenting with acute vomiting, evaluating their effects within the first 24 hours. A total of 40 cats with vomiting were enrolled and randomly allocated to receive maropitant (n=20), and ondansetron (n=20). A single subcutaneous dose of 1 mg/kg/day maropitant and 0.4 mg/kg/day ondansetron was administered. All cats were subjected to clinical evaluation for vomiting and nausea consisting of appetite and activity scores, vomiting/nausea scores (visual analog scale and numerical rating scale), and pain assessment, at 0 min, 30 min, 4 h, and 24 h. There was no time-dependent statistical difference between maropitant and ondansetron group for the activity-appetite score, pain score, visual analog scale, and numerical rating scale (p > 0.05), however, a significant decrease (p < 0.05) was observed in the numerical rating scale, pain score, and visual analog score after the application compared to the pre-application period in each group. Similarly, activity and appetite score of inter-groups increased (p < 0.05) at the end of the observation period. This research indicates that a single dose of ondansetron and maropitant could effectively control vomiting and nausea within the first 24 h with similar antiemetic effectiveness. Additionally, clinical scoring to predicting vomiting and nausea in cats could be a valuable tool for antiemetic drug choice.